A multi-function IEC 61850 packet generator based on FPGA. (25th May 2016) - Wei, Wei; Li, Hong-bin; Cheng, Han-miao
Abstract: An IEC 61850 packet generator is used to produce IEC 61850-9-2 packets by simulating the merging unit and testing the IEC 61850 digital device. While the existing IEC packet generator can produce ideal digital without any noise, it does not take into account the fact that the merging unit output signal packets will be inevitably superimposed with noise. Since the International Electrical Commission standard of the electronic current transformer specifies the minimum output signal-to-noise ratio of the merging unit to be 30 dB, and the signal superimposed with noise will influence the operation performance of the digital device, it is necessary to design a multi-function IEC 61850-9-2 packet generator for a digital device test. Therefore, in this paper, a multi-function IEC 61850 packet generator has been developed, which not only can output various IEC 61850-9-2 packets, but also can add white Gaussian noise to the signal for digital device testing. By testing three digital electricity meters from different manufacturers, we showed that the error of the digital electricity meter is significantly larger when the signal packet is superimposed with noise. Also when the signal-to-noise ration is 30 dB, the error of one of the meters exceeds the allowed range of the accuracy class. This indicates that the noise testing and the noise setting function of the system has an important role in the testing of a digital device.